2017
DOI: 10.20307/nps.2017.23.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Conditions for Active Compounds of Herbal Medicinal Formula, DF, by Response Surface Methodology

Abstract: − DF formula is comprised of three traditional herbs, Ephedra intermedia, Rheum palmatum and Lithospermum erythrorhizon, and locally used for treating of the metabolic diseases, such as obesity and diabetes in Korea. We tried to optimize the extraction conditions of two major components, (−)-ephedrine and (+)-pseudoephedrine, in DF formula using response surface methodology with Box-Behnken design (BBD). The experimental conditions with 70% for EtOH concentrations, 4.8 hour for extraction hours and 8.7 times f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Similar to CCD, the BBD can be applied for optimization study including extraction process, product enhancement, and chromatographic separation. These designs were widely used to optimize several parameters of extraction such as extraction time, extraction temperature, extraction number, solid to liquid ratio, solvent selection, and solvent concentration (Anuar et al, 2013;Jeong et al, 2017;Sousa et al, 2014;Yoo et al, 2018). For specific extraction technique, namely, decoction process, parameters including decocting temperature, total decocting time, and water-to-medicinal sample ratio were evaluated (Ha et al, 2018;Zhang et al, 2017).…”
Section: Box-behnken Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to CCD, the BBD can be applied for optimization study including extraction process, product enhancement, and chromatographic separation. These designs were widely used to optimize several parameters of extraction such as extraction time, extraction temperature, extraction number, solid to liquid ratio, solvent selection, and solvent concentration (Anuar et al, 2013;Jeong et al, 2017;Sousa et al, 2014;Yoo et al, 2018). For specific extraction technique, namely, decoction process, parameters including decocting temperature, total decocting time, and water-to-medicinal sample ratio were evaluated (Ha et al, 2018;Zhang et al, 2017).…”
Section: Box-behnken Designmentioning
confidence: 99%
“…Optimizing the experimental conditions in the laboratory to extract (−)-ephedrine and (+)-pseudoephedrine (Jeong et al, 2017) Curcuma syrup Optimizing HPLC condition Huang-Qi-Liu-Yi Tang (an herbal formula) Optimizing the decoction conditions (Zhang et al, 2017)…”
Section: Lithospermum Erythrorhizonmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheum palmatum L. (RPL), belonging to the Polygonaceae family, is a known herbal medicine in traditional Chinese medicine (TCM), and modern pharmacological studies have found that RPL has various pharmacological activities including anti-inflammatory, anti-tumor, bacteriostatic, hemostatic, lipid-lowering, and hypotensive effects ( Lee et. al., 2012 ; Jeong et al., 2017 ; Park et al., 2018 ). In addition, a growing number of studies have found that RPL extract and its monomers can induce apoptosis in various human cancer cells ( Chiu et al., 2009 ; Ma et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the leptin signaling pathway, PTP1B has the function of binding and dephosphorylation for Janus kinase 2, which is normally phosphorylated in response to leptin binding to the leptin receptor to trigger a feeling of satiety . Knockout studies in mice have shown that PTP1B-deficient mice exhibit increased insulin sensitivity and obesity resistance. , These findings have motivated scientists to develop PTP1B inhibitors as potential therapies for diabetes and obesity. , Furthermore, recent findings have suggested that inhibiting PTP1B may have important applications in the treatment of cancer and inflammation. In addition, PTP1B has recently emerged as a regulator of a variety of processes within the central nervous system, which may have implications in treating neurological disorders. However, discovering selective PTP1B inhibitors with ideal pharmacological properties continues to be a challenge because of the low selectivity and the highly charged nature of the PTP1B catalytic domain . Natural products have recently gained attention as novel PTP1B inhibitors, because they tend to be more efficacious in cells with high structural diversity when compared to synthetic compounds …”
mentioning
confidence: 99%